Divided We Stand : American Workers and the Struggle for Black Equality - Nelson, Bruce, 1940- (Book collections on Project MUSE., 2001)
"Divided We Stand includes vivid examples of white working-class "agency" in the construction of racially discriminatory employment structures. But Nelson is less concerned with racism as such, than with the concrete historical circumstances in which racialized class identities emerged and developed. This leads him to a detailed and often fascinating consideration of white working-class ethnicity, but also to a careful analysis of black workers - their conditions of work, their aspirations and identities, their struggles for equality. Making its case with passion and clarity, Divided We Stand will be a compelling and controversial book."--Jacket.